The impact of dapagliflozin on glucose excursions related to early proatherogenic derangement in the aortic wall - Agnieszka Stelmaszyk; Anna Wesołowska; Karolina Pomieczyńska; Saule Iskakova; Magdalena Frydrychowicz; Grzegorz Dworacki; Marzena Dworacka (Elsevier, 2018)
Introduction: Cardiovascular risk in the course of diabetes depends greatly on glycemic variability which is even more significant than chronic hyperglycemia. Optimal management of diabetes involves a multidisciplinary approach focused in particular on decreasing the risk of atherosclerosis. Therefore, our purpose was to evaluate the impact of dapagliflozin on glucose excursions and related proatherogenic changes in the aortic wall. Methods and materials: Animal model of type 2 diabetes rich-fat/STZ rats was used. Wistar rats were randomized into 3 groups: dapagliflozin-treated with glucose excursions, placebo-treated with glucose excursions and placebo-treated with stable diabetes. Dapagliflozin was administered once a day, 1 mg/kg, for 8 consecutive weeks. Glucose levels were measured twice a week at fasting and postprandially. The samples of aortas were taken for histopathological and immunochemistry examinations at the end of the experiment. The derangement in the aortic wall and the distribution of CD68+ cells in the aorta were considered early signs of atherosclerosis. Results: Dapagliflozin reduced glucose excursion to the level characteristic for stable, well-controlled diabetes. It was related to a significant decrease in histopathological changes which were observed in the placebo-treated rats with glucose variability. Dapagliflozin significantly reduced also the accumulation of CD68+ macrophages in the aortic adventitia. Conclusion: Dapagliflozin provides not only mere beneficial regulation of metabolic status with the depletion of glucose variability, but is also helpful in the prevention of early atherosclerosis related to the course of diabetes type 2. Keywords: Atherosclerosis, Cardiovascular disease, Type 2 diabetes, Glucose excursions, Dapagliflozin